Potential use of residual soil and geosynthetic - Henry, Krisdani (2010)
Rainfall-induced slope failures frequently occur in residual soil slopes in tropical regions. Previous research works indicated that the main cause of slope failure in residual soil slopes is rainfall infiltration. The infiltrating water decreases matric suction in the soil and consequently reduces shear strength of the residual soil slopes. One of the possible preventive measures for the rainfall-induced slope failures is the use of a soil cover to minimize water infiltration into the slope. Previous research works showed that a capillary barrier system could be used as a soil cover to minimize rainfall infiltration. A capillary barrier is a soil cover consisting of a fine-grained soil layer overlying a coarse-grained soil layer. In this study, the use of a local residual soil derived from Bukit Timah Granite as the finegrained layer in a capillary barrier system was investigated.